Jejak Pesantren di Madura; Dari Islamisasi hingga Dinamika Lembaga - Evarianisa Endang Trisnani (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2021)
Many researchers need to work hard to build the history of the Islamization of Madura so that it is fully structured. This is because facts have mingled with legend. Therefore, this study seeks to identify the Islamization of Madura with historical facts obtained from library and field data. The approach used in this research is qualitative with historical sociology perspective. The results of this study reveal that there are two paths to Islamization of Madura, namely the royal path and the path of the da'i or better known as Walisongo. The royal line necessitated that the Islamization of Madura was through the royal leaders and nobles. Because the kings are Muslim, their descendants follow Islam and are followed by the residents under them who also embrace Islam. Meanwhile, from the da'i line, the process of Islamization of Madura is a continuation of the mega project of Islamization of the Nusantara which was very massive between the 7th century to the 15th century. Both paths are strengthened by pesantren - as typical Islamic educational institutions of the Nusantara - which are spread throughout Madura.